Efficacy, safety, and tolerability of adjunctive perampanel in patients from China with focal seizures or generalized tonic‐clonic seizures: Post hoc analysis of phase III double‐blind and open‐label extension studies - Weiping, Liao (CNS Neurosci Ther, 2020)
AIMS: This post hoc analysis assessed the efficacy and safety/tolerability of adjunctive perampanel in patients from China (aged ≥12 years) with focal seizures (FS), with/without focal to bilateral tonic‐clonic seizures (FBTCS), or generalized tonic‐clonic seizures (GTCS). METHODS: Study centers in China were identified using data from five double‐blind, randomized, phase III studies of adjunctive perampanel (2‐12 mg/day) and their open‐label extensions (OLEx). Efficacy assessments included median percent reduction in seizure frequency per 28 days, and 50% and 75% responder and seizure‐freedom rates. Safety/tolerability assessments included monitoring of treatment‐emergent adverse events (TEAEs). RESULTS: Overall, 277 patients (placebo, n = 79; perampanel, n = 198) were included in the double‐blind safety analysis set. The full analysis set comprised 274 patients (FS, n = 238 [placebo, n = 60; perampanel, n = 178]; FBTCS, n = 120 [placebo, n = 31; perampanel, n = 89]; GTCS, n = 36 [placebo, n = 18; perampanel, n = 18]). Median percent reductions in seizure frequency for placebo vs perampanel were as follows: 16.6% vs 32.4% (FS; P < 0.05) and 39.1% vs 48.2% (FBTCS; not significant [NS]) at 4‐12 mg/day, and 37.9% vs 82.6% (GTCS; NS) at 8 mg/day; 50% responder rates were 31.7% vs 37.4% (FS; NS), 48.4% vs 51.9% (FBTCS; NS), and 33.3% vs 61.1% (GTCS; NS), respectively. Seizure‐freedom rates were 1.7% vs 9.2%, 16.1% vs 25.3%, and 16.7% vs 44.4%, respectively (all NS). Overall, 262 patients entered the OLEx (FS, n = 228; GTCS, n = 34). Perampanel was efficacious for up to four years for FS and FBTCS and up to two years for GTCS. Across the double‐blind and OLEx studies, TEAEs were reported in 65.7% and 81.3% of perampanel‐treated patients, respectively; the most common was dizziness. Efficacy and safety/tolerability outcomes were generally similar between Chinese and non‐Chinese patients. CONCLUSION: Adjunctive perampanel (up to 12 mg/day) may be a suitable treatment for Chinese patients with FS, with/without FBTCS, or GTCS, with similar efficacy and safety/tolerability compared to non‐Chinese patients.